PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KANCING GEMERINCING DI MAS DARUL ULUM KUBU RAYA - Rasip, Rasip; Mirza, Ade; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aimed to know and to find out the effectiveness of talking chips to teach trigonometry to the grade x studens of MAS Darul Ulum Kubu Raya. The research participants were the class X IPA 2. The data were collected through the measurement technique in a written test and the observation to find out the effectiveness of talking chips technique in teaching-learning process. The findings showed  that there were some points. There are (1) The teacher’s rule in teaching learning process was (3,41) categorized as good; (2) the student’s activiness was ( 65,76%) categorized as active; (3) The student’s clasical achivement was (66,67%); (4) The student’s response was (84,79%) categorized as positive. In short, the use of talking chips was not affects the teaching trigonometry in the grade x studen’s of class X IPA 2 in MAS Darul Ulum Kubu Raya. Keywords: Cooperative Learning, Talking Chips, Effectiveness, Trigonometry